Performance and Configuration Analysis of Tracking Time Anti-Windup PID Controllers - Muniru Olajide Okelola; David Oluwagbemiga Aborisade; Philip Adesola Adewuyi (Universitas Ahmad Dahlan, 2020)
As popular as the application of Proportional Integral Derivative (PID) controller is, issues relating to saturation effects are still being addressed using different techniques. Amongst such techniques are clamping anti-windup technique and back-calculation anti-windup techniques which primary prevent the integral term of the PID control action from reaching saturation. Separate tracking time technique was applied to both cases of anti-windup techniques investigated in this research unlike the conventional tracking time. These anti-windup controllers were used to control the operation of a motorized globe valve. The results obtained after simulation in MATLAB Simulink environment showed that both techniques gave similar outputs with a stable response of magnitude 0.95 at 1.5 seconds settling time when a unit step reference input signal was applied as compared to conventional PID controller that had an overshoot of 1.04 before settling to a magnitude of 1.0 at 1.5 seconds. Vibration, instability, and operational distortion were experienced when the anti-windup techniques were cascaded. The same responses were obtained when their outputs were combined to control the motorized globe valve. Other interesting mathematical models of important components are contained in the full paper.